What is the role of memory in consumer–brand relationship? Insight from sport industry - Cayolla, R.; Loureiro, S. M. C. (Journal of Creative Communications, 2021)
We live in a time when symbolism is of enormous priority. Memories are a particularly important part of the construction of individual identity and the subsequent relationships established, personal and with the loved brands. Previous research in psychology and neurosciences on negativity effect claims that negative events have more impact than positive ones. In an emotional context like the sports industry, being a fan has implications at all levels: psychological, mental and behavioural. Deepening the theme of memory from a psychological perspective, the present study theorises about the hypothesis of positivity effect in memory in the behaviour of sport fans in consumer neuroscience studies. Theoretical contribution and managerial suggestions are presented, in addition, as direction for further research.